Male’s Knowledge and Awareness about AIDS/STDs in Rajshahi District of Bangladesh - Rahman, Mosiur (Dhaulagiri Journal of Sociology and Anthropology, 2008)
As there is no cure to get rid of the unbearable sufferings from these diseases, prevention is the only solution to get rid of HIV/AIDS and STDs. Raising awareness among men about the long run effects of these diseases is one of the prime objectives of reproductive health programs currently executing in the world. Our study pays attention to get an idea of men's perception about these types of reproductive health problems. Findings reveal that about 87 percent men aware about HIV/AIDS and comparatively women were found same aware of AIDS. Only 54.8 percent men are found aware STIs, and more than 45 percent of the respondents have no knowledge of STIs. This indicates men's careless ness about these diseases. Mass media plays a great role in growing awareness about HIV/AIDS. Electronic, print media and interpersonal communication were the main sources of knowledge. About 30 and 40 percent men and women heard of AIDS from two sources respectively. It was found that majority of the male said uncontrolled sexual relation is the major reason of spreading AIDS. Although men's communication with their spouses can help in preventing AIDS but a large portion respondent don't talk to their spouses about preventing AIDS. Findings also elucidate that education, residence, religion, occupation, and mass media facility are the significant factors to influence AIDS knowledge among men. Key words: HIV/AIDS, STDs, Logistic Regression Analysis, Bangladesh DOI = 10.3126/dsaj.v2i0.1367 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.253-270